Design and implementation of P2P reasoning system based on description logic. (30th May 2013) - Wan, Hai; Yu, Yang; Zheng, Jian–tian
P2P reasoning system can answer queries from not only each peer's local theory but also some other peers related with sharing part of its vocabulary. This paper concentrates on P2P reasoning technology based on description logic, trying to provide an intelligent solution for searching network resources. A P2P reasoning algorithm suitable for description logic called DL–DeCA is proposed in this paper, as well as its system implementation of DL–P2PRS (description logic P2P reasoning system). Experiment results show that DL–P2PRS can work correctly and effectively.